The Value of 68Ga-PSMA PET/CT Following Equivocal 18F-NaF PET/CT in Prostate Cancer Patients - Claus Madsen (Diagnostics, 2020)
Background: Inconclusive bone scans are a challenge but there is no consensus about follow-up imaging. We evaluated the use of 68gallium-labelled prostate-specific membrane antigen (68Ga-PSMA) PET/CT if 18F-sodium fluoride (18F-NaF) PET/CT was inconclusive. Methods: This retrospective study included patients with no previously known bone metastases who had one or more equivocal bone lesions on 18F-NaF PET/CT and underwent additional 68Ga-PSMA PET/CT. The bone lesions were deemed as true metastases or not based on follow-up by surveying supplemental imaging modalities and hospital records. A subgroup of patients with “most valid follow-up” was created, which included patients with unmeasurable PSA after prostatectomy or subsequent imaging (additional 18F-NaF PET/CT, 68Ga-PSMA PET/CT, CT, or MRI). Results: Of the 2918 patients referred for 18F-NaF PET/CT from the department of urology in the inclusion period, 51 (1.7%) were inconclusive regarding bone metastases and underwent additional 68Ga-PSMA PET/CT. Thirteen of these patients (25%) were ultimately diagnosed with bone metastases. Patient-based sensitivity, specificity, and accuracy of additional 68Ga-PSMA PET/CT were 100%, 95%, and 96%, respectively. In patients with “most valid follow-up”, the same parameters were 100%, 93%, and 94%, respectively. Conclusion: 68Ga-PSMA PET/CT is an excellent complementary modality in when 18F-NaF PET/CT is equivocal.